Multi-Objective Optimization of Urban Air Transportation Networks Under Social Considerations - Nikolas Hohmann; Sebastian Brulin; Jurgen Adamy; Markus Olhofer (IEEE Open Journal of Intelligent Transportation Systems)
This work proposes and investigates a solution approach to the urban air transportation network optimization problem, considering the perspectives of different stakeholders, including societal interests. Given logistic hub positions and a set of optimized paths connecting them pairwise, we aim for a Pareto-optimal and three-dimensional air corridor network structure. This work demonstrates a way to merge the given paths into a network and provides a framework to optimize the network further regarding multiple objectives. It proposes three objective functions that evaluate the network from the economic perspectives of network providers and users and the city residents’ social point of view. Using geospatial data from Frankfurt, Germany, we conducted different experiments including and excluding the social objective function under a varying input set of pre-optimized paths. Our analysis showed that taking social aspects into account results in traffic networks whose increase in social acceptance far outweighs the extra monetary costs. We conclude that it is beneficial to integrate social criteria into optimization problems when the solutions obtained are the basis for decisions in the area of conflict between the economy and human welfare.